Disputed authorship in US Law - McMenamin, Gerald (International Journal of Speech, Language and the Law, 2004)
The purpose of this note is to recognize the significant contribution of Tiersma and Solan (2002) to forensic linguistics, but to oppose their classification of disputed authorship cases as a ‘problem area’ in the field, that is, which they define as an area of expert linguistic testimony associated with judicial reluctance to admit such testimony. In contrast to their position, I submit that that disputed authorship cases be considered ‘non-problematic’ by their definition, that is, areas in which testimony by linguists has been repeatedly presented in and admitted by courts in the US and other countries. The basis for this proposal is threefold. First, cases cited to support the ‘problem area’ designation are either unlitigated matters from the media, cases wherein actual linguists did not proffer testimony, or not on point. Second, there is a significant body of disputed-authorship testimony based on linguistic observation and description, admitted by the courts over the years and affirmed on appeals. Third, there are growing numbers of cases in which courts around the world have admitted disputed-authorship testimony provided by linguists.